Place children’s education in Islam (Journal of Philosophy Culture and Political Science, 2018)
The article discusses the system of education in Islam, in particular, the place of parenting, subtle aspects of children’s education, the experience of the Prophet Muhammad in matters full attention to the children, Muslim foundations in the children’s upbringing, and others reveals the principles that adhere to the Prophet Muhammad in the education: Full attention, as a high level of responsibility in the upbringing and mercy, love, mischief reasonable, cooperative games, child permissible religion, not separating children by gender, unacceptable lies in education, the performance promises. However, addresses such topics as : treat with understanding for the misdeeds of children education, taking into account peculiarities of the child’s sex, positive parental example, not to provoke bad behavior in the child vaccination in childhood healthy lifestyle, purity, humanity, kindness, fundamentals of religion and Muslim morality.Key words: Child’s education, Islam, Muhammad, muslim.